Decolorization of direct dye in textile wastewater by ozonization in a semi-batch bubble column reactor - Turhan, Kadir; Turgut, Zuhal (ELSEVIER SCIENCE BV, 2009)
Decolorization of wastewater containing direct dye (Sirius Blue SBRR) by ozonization was studied in an attempt to abate pollution caused by textile dyeing houses and dye-producing plants. The decolorization process of the direct dye was carried out by bubbling ozone at the bottom of a bubble column reactor containing the dye solution. The effect of dye concentration, ozone dose, ozone-air flow rate and solution pH on the rate of decolorization was studied. The reaction rate was followed by measuring the dye concentration at different times of the decolorization process. The rate of dye oxidation was found to increase with increasing ozone concentration in the air-ozone and to decrease with increasing the dye concentration. The rate of dye oxidation increases with increasing the air-ozone flow rate and solution pH, reaches a maximum and then decreases with a further increase in the air-ozone flow rate. The results with the direct dyestuff wastewater showed that decolorization was remarkable under the basic condition of pH 12. A large amount of bubbles was formed at a high ozone-air flow rate. After 26 min of ozone treatment, decolorization was completed. From these results, the ozone treatment of the dyestuff wastewater in decolorization was excellent.
Keywords: Ozone; Sirius Blue SBRR; Wastewater treatments; Decolorization; Direct Blue 71; ADVANCED OXIDATION; OZONATION; INDUSTRY; EFFLUENT; COLOR; WASTEWATERS; OZONOLYSIS; H2O2/UV-C; REMOVAL; Engineering; Water Resources